Challenges of Online Medical Education During the COVID-19 Pandemic Faced by 3rd and 4th Year Medical Students of Sir Salimullah Medical College, Dhaka - Bristi, Priyanka Das; Zareen, Afshan; Sultana, Rehana; Salim, Airin; Hoshen, Md Minuddin; Das, Arnab (Eastern Medical College Journal, 2024)
Background: Online education is a form of education where students use their home computers through the internet staying away from academic institutions. Due to the emergence of the pandemic of COVID-19, the whole world is experiencing number of huge deaths along with widespread panic and uncertainty. Countries of the world are trying to fill the gap and minimize the losses of students caused by the ongoing pandemic. Objective: This study mainly explores the challenges of online medical education during COVID-19 pandemic faced by 3rd and 4th year medical students of Sir Salimullah Medical College, Dhaka, Bangladesh. Methodology: This Descriptive cross-sectional study was conducted in Sir Salimullah Medical College, Dhaka from January 2021 to December 2021. A weblink of survey was shared with 439 3rd and 4th year medical students and 309 responses were obtained. Data were collected by using pretested semi structured questionnaire by face-to-face interview and by online google form due to COVID-19 pandemic situation and sample were collected by purposive sampling. Result: Among 309 respondents, 60.2% were female and 39.8% were male, 95.8% respondents were Bangladeshi, 46.3% respondents’ family income were around 30000 taka, 64.4% respondents lived in city, 22% respondents faced some challenges regarding internet connection, 8.41% respondents faced knowledge about internet browsing, 5.18% respondents faced problem regarding time management and 3.8% respondents faced problem about the adaptation of new method of learning. Despite these challenges 59.2% of the respondents reported positive response about beneficial effect of online classes and half (52.8%) of the respondents were satisfied with online classes. Conclusion: In medical education face-to-face education is essential. But due to lockdown there was no scope of practical and face to face education during COVID-19 pandemic situation. This study showed that there were some positive and negative impacts of online education. Eastern Med Coll J. July 2023; 8 (2): 7-12